2018
DOI: 10.1158/1055-9965.epi-17-1102
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Neighborhood Characteristics on Treatment and Outcomes in Women with Ductal Carcinoma In Situ of the Breast

Abstract: This study examines associations of neighborhood characteristics with treatment and outcomes of ductal carcinoma (DCIS) of the breast. From the Missouri Cancer Registry, we identified 9,195 women with DCIS diagnosed between 1996 and 2011. A composite index using U.S. Census data and American Community Survey data was developed to assess census tract-level socioeconomic deprivation, and rural-urban commuting area codes were used to define rural census tracts. ORs and 95% confidence intervals (CIs) of the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Neighborhood socioeconomic deprivation and rurality were assessed on the basis of the census tract of a patient's residence at diagnosis. The composite socioeconomic deprivation indices for 2000 and 2010 were calculated separately on the basis of 21 variables from the 2000 and 2010 US Census, as described previously 12‐14 . On the basis of their nationwide distribution, index scores were divided into tertiles, with a higher tertile suggesting greater socioeconomic deprivation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neighborhood socioeconomic deprivation and rurality were assessed on the basis of the census tract of a patient's residence at diagnosis. The composite socioeconomic deprivation indices for 2000 and 2010 were calculated separately on the basis of 21 variables from the 2000 and 2010 US Census, as described previously 12‐14 . On the basis of their nationwide distribution, index scores were divided into tertiles, with a higher tertile suggesting greater socioeconomic deprivation.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of their nationwide distribution, index scores were divided into tertiles, with a higher tertile suggesting greater socioeconomic deprivation. Rural counties were defined as nonmetropolitan areas and were determined with the rural‐urban commuting area (RUCA) codes (4, 4.2, 5, 5.2, 6, 6.1, 7, 7.2, 7.3, 7.4, 8, 8.2, 8.3, 8.4, 9, 9.1, 9.2, 10, 10.2, 10.3, 10.4, 10.5, or 10.6) from the US Department of Agriculture 14 . The 2000 deprivation index and the 2000 RUCA codes were linked to the cases diagnosed between 2007 and 2009, and the 2010 deprivation index and the 2010 RUCA codes were linked to the cases diagnosed after 2009.…”
Section: Methodsmentioning
confidence: 99%
“…McDougall and colleagues studied colorectal cancer survivors in New Mexico and found that those who lived in rural areas were more likely to experience financial hardship and less likely to adhere to recommended follow-up care, highlighting the importance that place plays in affordable, accessible survivorship care (11). To examine the associations of neighborhood characteristics in Missouri with treatment and outcomes of ductal carcinoma in situ, Zhang, Liu, and colleagues used census tract-level socioeconomic deprivation and rural-urban commuting area codes to define rurality; although differences in treatment, but not outcome, were found, the authors suggest that larger studies using nuanced definitions of rurality are needed to refine our understanding the contribution of place to outcome (12). It is noteworthy that the definition, location, and composition of "rural" differ across the United States and these may affect the interpretation of the study findings included in this special issue.…”
Section: Bridging the Gap: Stories From The Fieldmentioning
confidence: 99%
“…Although geography alone cannot predict cancer risk, it can impact prevention, screening, diagnosis, and treatment opportunities. The articles in this special CEBP Focus issue on rural cancer control explore geographic disparities across the cancer control continuum in several distinct rural communities and map out potential paths to reach geographic health equity (7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…51 Explanations for racial differences in clinical outcomes are most likely a complex interplay between treatmentrelated disparities and socioenvironmental exposures. 80,81 Future research should leverage concepts such as allostatic load--a composite measure of physiologic dysregulation secondary to adverse socially patterned exposures (eg, poverty 82 )-to understand the implications of race and socioenvironmental factors on epidemiology, 83 treatment receipt, tolerability, and mortality, and identify targets for precision therapy, including biobehavioral intervention. 84 In future studies, several barriers must also be addressed to allow translational studies to improve DCIS management.…”
mentioning
confidence: 99%